TINJAUAN YURIDIS TERHADAP ANAK DIBAWAH UMUR YANG MELAKUKAN PELANGGARAN LALU LINTAS HINGGA MENGAKIBATKAN KECELAKAAN SAMPAI MENIMBULKAN KORBAN JIWA DI LINGKUNGAN PATROLI JALAN RAYA (PJR) KORLANTAS POLRI - Maulidiyono Dwiputra, Lian; Gultom, Potler (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
In this research, one form of traffic violation is a minor who drives a motorized vehicle and does not have a driving license (SIM). This research examines a) what is the juridical review of minors who commit traffic violations that cause accidents and cause fatalities in the area of ​​the National Police's traffic police highway patrol, b) what is the responsibility of minors who commit traffic violations that cause accidents and cause fatalities. The research method used in this research is through normative juridical research which is supported by interviewing sources and collecting data using library research. The conclusions of this research are: a) a judicial review of traffic accident cases involving minors. Minors are regulated by special laws, namely Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This law regulates various legal aspects related to minors who commit criminal acts, including traffic accidents. b) a child who is still a minor can be held responsible for the actions he has committed, based on the provisions of the child's age, as regulated in the provisions of the juvenile justice system, which regulates the imposition of sanctions based on the provisions of the child's age, namely over 14 years of age, as there is a requirement to look at age in determining sanctions as regulated in Law No. 11 of 2012, in Article 69 paragraph (1).